Pengembangan Pasar Malam di Cifest Cikarang: Sinergi Zona Industri, Perumahan, dan Daerah Pemukiman Untuk Kepuasan Pelanggan dan Keuntungan Bisnis - Sunarni Sunarni; Asral Asral; Kusnan Kusnan; Abdy Kurniawan Chaerul (Pusat Riset dan Inovasi Nasional, 2023)
This article discusses the development strategy of the night market at Cifest Cikarang, aimed at strengthening the synergy between the industrial zone, employee housing, and residential areas to improve customer satisfaction and business profits. Night markets have become popular in Indonesia not only as a place to shop but also as a place to relax and interact with others. Additionally, they provide positive impacts on the local economy by increasing traders' income and strengthening the synergy between industrial zones, employee housing, and residential areas. Developing night markets is, therefore, an essential strategy for the government and business actors. The authors review the literature on night markets and found that developing night markets in industrial zones can increase the attractiveness of the area for employees and the general public. Night markets can become an alternative place for shopping and relaxation different from conventional shopping centers. Additionally, night markets can strengthen the synergy between employees and the local community, providing access to high-quality and varied local products. However, businesses must consider factors affecting customer satisfaction such as product quality, availability, affordability, and adequate facilities when developing night markets. The authors conclude that in developing the night market at Cifest Cikarang, businesses must consider the characteristics of the industrial zone and employee housing surrounding it. Developing a night market that strengthens the synergy between industrial zones, employee housing, and residential areas can improve customer satisfaction and business profits. Moreover, businesses must consider factors such as product quality, price, and adequate facilities when designing an effective development strategy.